2019
DOI: 10.1111/jcpp.13128
|View full text |Cite
|
Sign up to set email alerts
|

Maternal object naming is less adapted to preterm infants’ than to term infants’ word mapping

Abstract: Background Term infants learn word–object relations in their first year during multisensory interactions with caregivers. Although preterm infants often experience language delays, little is known about how caregivers contribute to their early word–object learning. The present longitudinal study compared maternal naming and word learning in these infant groups. Methods Forty moderately preterm and 40 term infants participated at 6–9 and 12 months with their mothers. At each visit, mothers named two novel objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…From shortly after birth, infants preferentially direct their vision to social content and later maintain this preference when presented with multiple object arrays (Gliga, Elsabbagh, Andravizou, & 2019). Gaze studies in preterm infants have also shown a consistent pattern of reduced social attentional preference and learning, in both visual and auditory contexts (Frie, Padilla, Aden, Lagercrantz, & Bartocci, 2016;Gogate, 2020;Gogate, Maganti, & Perenyi, 2014;Imafuku et al, 2017;Imafuku et al, 2019;Pereira et al, 2017;Telford et al, 2016). However, the stability of these differences over time, and whether they contribute to the ontogeny of neurodevelopmental and/or cognitive impairment, is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From shortly after birth, infants preferentially direct their vision to social content and later maintain this preference when presented with multiple object arrays (Gliga, Elsabbagh, Andravizou, & 2019). Gaze studies in preterm infants have also shown a consistent pattern of reduced social attentional preference and learning, in both visual and auditory contexts (Frie, Padilla, Aden, Lagercrantz, & Bartocci, 2016;Gogate, 2020;Gogate, Maganti, & Perenyi, 2014;Imafuku et al, 2017;Imafuku et al, 2019;Pereira et al, 2017;Telford et al, 2016). However, the stability of these differences over time, and whether they contribute to the ontogeny of neurodevelopmental and/or cognitive impairment, is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Early divergence from this trajectory has been observed in children who later receive a diagnosis of autism (Chawarska, Macari, & Shic, 2013; Jones, Carr, & Klin, 2008), leading to the suggestion that reduced fixation on social content (hereafter, reduced social attentional preference) may be an early marker of atypical social cognition (Gogate, 2020; Imafuku, Kawai, Niwa, Shinya, & Myowa, 2019). Gaze studies in preterm infants have also shown a consistent pattern of reduced social attentional preference and learning, in both visual and auditory contexts (Frie, Padilla, Aden, Lagercrantz, & Bartocci, 2016; Gogate, 2020; Gogate, Maganti, & Perenyi, 2014; Imafuku et al, 2017; Imafuku et al, 2019; Pereira et al, 2017; Telford et al, 2016). However, the stability of these differences over time, and whether they contribute to the ontogeny of neurodevelopmental and/or cognitive impairment, is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The use of touch as a multimodal cue relevant for word boundaries and mapping referents to wordforms and its adoption for an attention‐modulating function are likely to work in an integrated fashion for infants' word learning. In fact, previous studies have shown that caregivers' greater use of synchronous multimodal labeling events is associated with heightened infant attention (Tincoff et al., 2019) and better learning of word‐object relations (Gogate, 2020; Gogate et al., 2006; Matatyaho & Gogate, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The mothers of these infants are at risk for maladjustment (Heidari et al, 2013). The results of studies show that mothers of preterm infants have more difficulty than mothers of term infants in adjusting to their maternal roles (Lee et al, 2009;Forcada-Guex et al,2011;Gogate, 2020). In the case of preterm birth, the process of adjusting to the developmental crisis of having a new infant and the situational crisis of having a preterm infant provides a variety of stressors for the new mother (Pyhälä et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A mother's ability to adjust to the stressors is related to the nature of the stimuli and to the mother's existing mode of adaptation. In other words, the more preterm the infant, the more intense the stressors that affect the mother's existing mode of adaptation (Gogate, 2020). A mother whose infant is admitted to the NICU has limited opportunities to care and interact with the infant, and this delays the acquisition of the maternal role (Rajabi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%